Catalytic Disproportionation of Formic Acid to Methanol by an Iridium Complex Immobilized on Bipyridine‐Periodic Mesoporous Organosilica. Issue 19 (6th September 2019) - Yamaguchi, Sho; Maegawa, Yoshifumi; Onishi, Naoya; Kanega, Ryoichi; Waki, Minoru; Himeda, Yuichiro; Inagaki, Shinji
Abstract: We report the first example of using heterogeneous Iridium (Ir) catalysts under atmospheric pressure conditions to achieve the catalytic disproportionation of formic acid to methanol. IrCp* complex (Cp*=pentamethylcyclopentadienyl (ɳ 5 ‐C5 Me5 )) was immobilized on the pore surface of the periodic mesoporous organosilica synthesized from a precursor mixture of ethane (Et) and 2, 2′‐bipyridine (BPy)‐bridged organosilanes (Ir‐Et‐BPy‐PMO). Ir‐Et‐BPy‐PMO showed unique catalysis with higher selectivity of methanol compared to homogeneous Ir‐BPy complexes. Furthermore, Ir‐Et‐BPy‐PMO exhibited high reusability without any noticeable decrease in activity for at least five times with no leaching of Ir species during the reaction. The increase in methanol selectivity of Ir‐Et‐BPy‐PMO would be attributed to the unique confinement effect in the mesochannels with their high aspect ratio for the retention of generated H2 /CO2, which suppresses the competing formic acid dehydrogenation and promotes the formic acid hydrogenation. Abstract : Catalytic disproportionation : Iridium complex immobilized on periodic mesoporous organosilica containing a bipyridine scaffold exhibited higher methanol selectivity in disproportionation of formic acid compared to equivalent homogeneous complexes, possibly due to the confinement effect of mesopores to retain the generated H2 /CO2 which suppress the excess formic acid dehydrogenation and promote the formic acid hydrogenation.